Przełom technologiczny w polskim e-biznesie w latach 2004-2005 - Małachowski, Andrzej (The technological breakthrough in Polish e-business between 2004-2005, 2005)
Between 2004-2005 many new solutions concerning informational and communications technologies appeared in Poland. These are, among others: UMTS technologies, cheap satellite Internet access, hot-spot (Wi-Fi) access development, Internet-Telephony services, Video on Demand, TV on Demand, CT/PDA integration, new e-business applications. The increase of these changes is a kind of technological break through, influencing most of all e-business environment. The I-C technologies development leads to a new quality creation in the area of communications services and ebusiness applications. All this makes another step towards an information society development, where all human activities are being activated in the I-C technologies sphere. The new technological solutions applied in Poland between 2004-2005, as well as their potential influence on e-business applications development are presented in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 235-247